An Entire Process Optimization Strategy for Comprehensive In Vivo Metabolite Profiling of Prucalopride in Rats Based on Ultra-Performance Liquid Chromatography With Q-Exactive Hybrid Quadrupole–Orbitrap High-Resolution Mass Spectrometry - Zuo, Lihua; Liu, Liwei; Yang, Yantao; Yang, Jie; Chen, Min; Zhang, Huafeng; Kang, Jian; Zhang, Xiaojian; Wang, Jiabo; Sun, Zhi (Frontiers in Pharmacology, 2021)
Prucalopride was widely used for chronic constipation, which is difficult to be adequately relieved by laxatives in adult patients in clinic. Due to the difficulty in metabolite identification, metabolic process of Prucalopride had not been investigated in vivo. In this study, an efficient strategy was proposed for comprehensive metabolite profiling of prucalopride after oral administration in rat plasma, urine and faeces samples. This strategy was composed of five steps. Fristly, the samples at multiple time points after oral administration were collected to increase the representativeness of the samples. Secondly, different sample preparation methods were investigated to obtain superior extraction efficiency. Thirdly, the raw data of test sample and blank sample was acquired using ultra Performance liquid chromatography with Q-Exactive hybrid quadrupole orbitrap high resolution accurate mass spectrometry under the positive and negative Full scan/dd MS2 mode. Fourthly, combined the mass defect filter and background subtraction model in soft of compound discovery was constructed to filter potential metabolites after retention time alignment and ion filtration, which could remove large amounts of interference ions. Besides, it can predict potential biotransformation, promoting to understand the drug how to metabolize. This provides multiple possibilities and prevents us conjecturing the potential metabolites blindly. Finally, the verification procedure was implemented through exporting the structure and MS2 spectrum to the analytical tool of Mass frontier. The proposed strategy significantly improved the targeted detection and identification for metabolites in vivo. A total of 47 metabolites were tentatively characterized in the plasma, urine and faeces samples after oral administration of Prucalopride. This paper could provide an valuable reference for systematic metabolite profile of drug in vivo.